Opportunities for preschoolers mathematical skills training using a digital mathematical application - D.A. Bukhalenkova; M.S. Aslanova; M.Sh. Mikhitaeva (Психологическая наука и образование)
Context and relevance. Digital devices are an integral part of the lives of most modern preschoolers. In this regard, the study of the developmental and educational potential of these devices is becoming an important and urgent task for modern science and practice. Objective. This study was aimed at exploring the possibilities of improving mathematical skills in preschoolers using a digital math application in situations of joint discussion with an adult or independent use of the application. Hypothesis. We assumed that preschoolers who use a digital math app in a situation of joint discussion with an adult will be more successful at completing math tasks for quantity and counting, as well as magnitude, than children who used the app on their own. Methods and materials. The study involved 64 preschoolers (42,1% of boys) aged 5-6 years, pupils of the senior kindergarten groups in Moscow. In the course of the study, preliminary testing of mathematical skills and the level of non-verbal intelligence in preschoolers was conducted; then, based on the diagnostic results, the children were divided into 2 experimental groups, each of which was given a series of six developmental classes. The final stage was the repeated testing of mathematical skills in children who took part in educational activities. Methods for comparing numbers, arithmetic skills, comparing intervals between numbers and a sense of number were used to evaluate mathematical representations of preschoolers about quantity, and tasks for measuring by measure and the ability to find a correspondence between objects in size were used to evaluate representations of magnitude. To diagnose the level of nonverbal intelligence, the technique of “Raven's Color Progressive Matrices" was used. Results. The results showed that more significant improvements in children's performance of counting and magnitude tasks occurred in children who had the opportunity to discuss math tasks performed in the application with an adult. Conclusions. The conducted research allows us to conclude that when using digital educational applications to train mathematical skills in preschoolers, the help and participation of an adult plays an important role.